Analisis Monitoring Produktivitas Kinerja Pada PT.ASP - Nita Rosa Damayanti (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
. PT AyuSyakira First established in 2013 and has been appointed by PT Prima Permata Putra Persada Perkasa as an Authorized Distributor / Agent Authorized to market the product High Speed ​​Diesel (HSD) for the region of South Sumatra (South Sumatra), Indonesia. As a supplier to industry needs, PT AyuSyakira First seeks to build its capacity as a distributor company that can serve all customers wherever fine. To meet these needs, the company has developed the nation's market to all regions of Sumatra Selatan.Sebagai company Commercial Fuel Distributor with complete facilities and services that a continuous supply for customers. Providing service supplies - fuel oil to its customers to improve the efficiency and effectiveness of the industry by providing high quality products, guarantee supply and timely. In help function PT.ASP entered into a collaboration to monitor performance by listing the reports submitted in the form of electronic reports to do an evaluation of each month. Through the process of data collection there is a possibility of duplication statements that cause inaccuracies such data and the evaluation process is slow. See the existing problems will be created in the application and analysis in order to minimize the problems that arise and improve the evaluation process. In this research, applications created with the framework concept model viewer controller (MVC). System development methods in this study is an incremental process models). In the final phase is expected to reduce the occurrence and ketidaakurasian duplication of data, as well as facilitate and accelerate the performance evaluation PT.ASP Palembang.